A phase II study to evaluate lenalidomide in combination with metronomic-dose cyclophosphamide in patients with heavily pretreated classical Hodgkin lymphoma. (June 2015) - Rueda, Antonio; García-Sanz, Ramón; Pastor, Miguel; Salar, Antonio; Labrador, Jorge; Quero-Blanco, Cristina; Casanova, Maria; Provencio, Mariano; on behalf of Gotel and Geltamo
Abstract Background. Relapsed or refractory (R/R) classical Hodgkin lymphoma (cHL) after autologous stem cell transplantation (ASCT) remains a challenge. For these patients treatments with different mechanisms of action rather than classical chemotherapy are needed. Patients and methods. Patients with R/R cHL after ASCT were recruited in a phase II trial (EUDRA CT: 2009-016588-12). Lenalidomide was administered at 20 mg/day for 21 days and cyclophosphamide at 50 mg/day for 28 days (cycles every 28 days). Dose escalation for lenalidomide was permitted. In 2009 we considered that this treatment would be promising if response rate were over 60% and a Simon two-stage binomial design was used to calculate the sample size. A total of 46 patients were planned but the trial would be stopped if less than seven responses after four cycles were obtained in the first 16 patients. Results. The trial was closed early because only five responses were observed after four cycles in the first 16 patients included. Median age was 34 years (18–77). The median number of previous lines was five (2–6). At inclusion, 10 patients were primary refractory and 11 refractory to the last therapy. A total of 110 cycles were administered, with grade ≥ 3 toxicity in 43 cycles (39%). One non-neutropenic patient developed septic shock resulting in death. An ORR of 38% (1 CR and 5 PR) was observed and a total of 10 patients (62%) achieved clinical benefit. Median progression free survival and overall survival were seven and 19 months, respectively. With a median follow-up of 19 months (3–38+), three-year progression-free and overall survival were 6% and 31%, respectively. Conclusion. The optimistic assumptions of this trial led to an early closure. However, the promising clinical benefit observed with the oral combination of lenalidomide and metronomic cyclophosphamide may justify its use for outpatient palliative treatment.